HARGA AIR UNTUK IRIGASI PADI SAWAH DI KABUPATEN BADUNG - I Made Sudarma (Environmental Research Center (PPLH) of Udayana University, 2015)
The research was conducted at Badung Regency from May to August 2012. BadungRegency determined as the study sites intentionally (purposive sampling) withconsideration Badung Regency is utilizing the highest Ayung river water for irrigation thananother regencies/city in Bali. Water pricing were analyzed by the Value Marginal Product(VMP) which derived from equation of the Cobb- Douglas production function. The analysisshowed that the size of area plantation, seed, fertilizer, pesticide, labor and water (irrigation)have real impact on rice production and by using the VMP analysis found that the price ofwater for irrigation is Rp 314.000/ha/season. The price paid is higher than the water fee forSubak, that is Rp 100,000/ha/season for active members and two-time for inactive members.Even the results of the calculations show that the maximum water price paid by farmers isgreater than subak fees, the government can not impose the maximum water pricing approachto the farmers. It is based on the consideration that the agricultural sector is still the sectorthat needs to be subsidized because it involves the interests of a political, economic, social,cultural and religious.